Involvement of specific macrophage-lineage cells surrounding arterioles in barrier and scavenger function in brain cortex. - Mato, M (1996)
The transport of solutes between blood and brain is regulated by a specific barrier. Capillary endothelial cells of brain are known to mediate barrier function and facilitate transport. Here we report that specific cells surrounding arterioles, known as Mato's fluorescent granular perithelial (FGP) cells or perivascular microglial cells, contribute to the barrier function. Immunohistochemical and in situ hybridization studies indicate that, in normal brain cortex, type I and type II macrophage scavenger receptors are expressed only in FGP/perivascular microglial cells, and surface markers of macrophage lineage are also detected on them. These cells mediate the uptake of macromolecules, including modified low density lipoprotein, horseradish peroxidase, and ferritin injected either into the blood or into the cerebral ventricles. Accumulation of scavenged materials with aging or after the administration of a high-fat diet results in the formation of honeycomb-like foam cells and the narrowing of the lumen of arterioles in the brain cortex. These results indicate involvement of FGP/perivascular microglial cells in the barrier and scavenger functions in the central nervous system.